2008
DOI: 10.1111/j.1600-0838.2007.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

The Enduro motorcyclist's wrist and other overuse injuries in competitive Enduro motorcyclists: a prospective study

Abstract: According to public opinion, Enduro motorcycling is a dangerous sport. Little is known about overuse injuries in connection with this sport. The study consisted of two phases. Phase 1 was planned as a prospective feasibility study for phase 2. The latter was initiated as a prospective investigation, comprising a random sample of the participants of phase 1. Enduro motorcyclists were interviewed with a prepared questionnaire. Clinical examinations were performed immediately before, and after, a major Enduro rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 11 publications
0
33
0
2
Order By: Relevance
“…In our collective, the incidence of carpal tunnel like syndromes was significantly increased after the race and significantly related to the saddle-pedal-distance. A significant occurrence of paraesthetic sensations in the area of the media nerve was reported by off road motorcyclists [3] The authors did not correlate their findings with the adjustment of the motorbike.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our collective, the incidence of carpal tunnel like syndromes was significantly increased after the race and significantly related to the saddle-pedal-distance. A significant occurrence of paraesthetic sensations in the area of the media nerve was reported by off road motorcyclists [3] The authors did not correlate their findings with the adjustment of the motorbike.…”
Section: Discussionmentioning
confidence: 81%
“…Due to vibrations and shocks it seems obvious that especially in the lumbar spine, in the hands, the knees and the feet, overuse injuries may occur in high numbers. In road cycle racing, overuse injuries are reported of the median nerve in the carpal tunnel [2], this is observed in off-road motorcyclists as well [3] the ulnar nerve in Guillon's Canal [2] the perineal nerve, the cervical [4] and lumbar spine and in the knees. Although recent studies have reported injuries in recreational and competitive off-road biking [5][6][7][8][9][10] little is known about overuse injuries in competitions [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the possible relationship between the use of motorcycles and the risk of developing CTS-like symptoms has been explored very little; two studies [10,15] indicate a correlation between the use of motorcycles and CTS-like symptoms. Sabeti-Aschraf et al[16] hypothesize that motorcycling is likely to affect the median nerve. The acceleration values measured in this case-report are comparable with those found in other studies, measured on various types of equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Several lesions such as vertebral fractures leading to paralysis, permanent handicap, and lethal injuries have been described in connection with motocross accidents 2 . Few published data concerning overuse syndromes associated with off‐road motorcycles, such as carpal tunnel‐Raynaud‐like symptoms and reduced forearm muscle force, have already been described 3 . In this study, all painful body regions including the hand/wrist, forearm, elbow, shoulder, cervical and lumbar spine, knee and ankle joint were registered, and the pain was analyzed.…”
Section: Case Reportmentioning
confidence: 99%